Association of dietary fat intake with skeletal muscle mass and muscle strength in adults aged 20–59: NHANES 2011–2014 - Wang, Shijia; Zhang, Yu; Zhang, Dandan; Wang, Fang; Wei, Wei; Wang, Qiong; Bao, Yuanyuan; Yu, Kang (Frontiers in Nutrition, 2024)
Background: Sarcopenia, a progressive loss of skeletal muscle mass and strength, needs to initially prevent in the twenties. Meanwhile, there is a lack of research on the effects of fat consumption on skeletal muscle mass and strength in adults aged 20-59. We aimed to assess associations between dietary fat intake and skeletal muscle mass, as measured by appendicular lean mass adjusted for body mass index (ALMBMI), and muscle strength, as represented by handgrip strength adjusted for body mass index (GSMAXBMI), among adults aged 20-59.Methods: Dietary fat intake per kilogram of actual body weight was assessed using two 24-hour recalls, while ALM and GSMAX were measured using DXA and a handgrip dynamometer， respectively. A weighted multiple linear regression model was employed to analyze the association between dietary fat intake and skeletal muscle mass, utilizing data from the National Health and Nutrition Examination Survey spanning from 2011 to 2014. To assess the non-linear relationship and saturation value between dietary fat intake and skeletal muscle mass, a smooth curve fitting approach and a saturation effect analysis model were utilized.The study comprised a total of 5356 subjects. After adjusting for confounding factors, there was a positive association observed between dietary fat intake and ALMBMI as well as GSMAXBMI.